2005
DOI: 10.1074/jbc.m408190200
|View full text |Cite
|
Sign up to set email alerts
|

Bid Mediates Apoptotic Synergy between Tumor Necrosis Factor-related Apoptosis-inducing Ligand (TRAIL) and DNA Damage

Abstract: The death ligand, TRAIL (tumor necrosis factor-related apoptosis-inducing ligand), has shown great promise for inducing apoptosis selectively in tumors. Although many tumor cells are resistant to TRAILinduced apoptosis alone, they can often be sensitized by co-treatment with DNA-damaging agents such as etoposide. However, the molecular mechanism underlying this therapeutically important synergy is unknown. We explored the mechanism mediating TRAIL-DNA damage apoptotic synergy in human mesothelioma cells, a tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 42 publications
1
55
0
Order By: Relevance
“…Earlier studies have shown that the overexpression of a dominant negative Bid construct inhibited apoptosis induced by both the Fas and TRAIL receptors in Jurkat cells (Werner et al, 2002), and Bid has been reported to regulate the synergy between TRAIL and epotoside in M28 and REN cells (Broaddus et al, 2005). We found that Bid is critical for FLIP silencing-induced processing of caspase 3 and cell death in the HCT116 and HT29 cells, indicating that mitochondrial activation is required for cell death to occur.…”
Section: Discussionsupporting
confidence: 49%
“…Earlier studies have shown that the overexpression of a dominant negative Bid construct inhibited apoptosis induced by both the Fas and TRAIL receptors in Jurkat cells (Werner et al, 2002), and Bid has been reported to regulate the synergy between TRAIL and epotoside in M28 and REN cells (Broaddus et al, 2005). We found that Bid is critical for FLIP silencing-induced processing of caspase 3 and cell death in the HCT116 and HT29 cells, indicating that mitochondrial activation is required for cell death to occur.…”
Section: Discussionsupporting
confidence: 49%
“…Another possible mechanism was proposed by Broaddus et al (2005). Their data suggest that the synergistic effect between TRAIL and other DNA-damaging agents depends on BH-3 only protein, Bid.…”
Section: Discussionmentioning
confidence: 97%
“…In other cell types, however, the mitochondrial pathway was essential for the combined effect. Specifically, in DU145 prostate carcinoma and HCT-116 colon carcinoma, the combined effect of IR and TRAIL relied on Bax (Ravi and Bedi, 2002;Wendt et al, 2005), in M28 mesothelioma it relied on Bid (Broaddus et al, 2005) and in a renal cell carcinoma it required Caspase-9 (Ramp et al, 2003). Jurkat cells are classically defined as type II cells that require a mitochondrial contribution to After 15 h incubation, cells were stimulated with FLAG-TRAIL precoupled to biotinylated anti-FLAG antibody for the indicated periods of time.…”
Section: Discussionmentioning
confidence: 99%